Implementation of Jackson Queueing Network in General Polyclinic and Dental Polyclinic Patient Services at Jelekong Health Center - Rasyid, Thariq Ahmad; Supian, Sudradjat; Nahar, Julita (International Journal of Global Operations Research, 2023)
The buildup in the service system is generally caused because service facilities cannot meet service needs, so service users need time to use the facilities. Health Center is one of the facilities that provide services in the health sector. However, the number of doctors needed in health centers in Indonesia has yet to be met, and the number of patients who are never empty every day causes a buildup in the service system. The application of the service network system using the open Jackson queueing network can model the optimal service system and analyze its performance. The observation method was used to observe patients' arrival and departure times at the Jelekong Health Center, especially in the registration section, general polyclinic, dental polyclinic, and pharmacy, for three days. There was an increase in patient waiting time before being served and time in the system at the general polyclinic after implementation, so one additional service facility was added. Meanwhile, the dental polyclinic experienced decreased patient waiting time before being served and time in the system, so there was no need to add service facilities.